THE EFFECT OF PERCEIVED EASE OF USE, PERCEIVE OF USEFULNESS, PERCEIVE RISK AND TRUST TOWARDS BEHAVIOR INTENTION IN TRANSACTION BY INTERNET - Yan Ari Nugroho (Business and Entrepreneurial Review, 2009)
This study aims to analyze the factors that influence consumer intentions to do transaction in e-commerce, which includes factors of easy to use, effectiveness of risk and trust. It also aims to analyze the potential development of new technology through consumer behavioral intentions to use new information technology by providing information about market demand for the development of information technology to businesses to further strengthen the company’s sales strategy. The research method used multiple regressions to find out about the influence of independent variables on the dependent variable by using hypotheses. The number of samples required for this research is 100 respondents. The result showed that the four variables namely Perceived Ease in Use, Perceived Usefulness, Perceived in Risk, and Trust have significant effect on consumer interest in transacting over the internet. Also Perceive in Risk is a variable that has the most dominant influence on consumer intentions to transact over the Internet